A study on variations of Bottlenecks in Software Testing - S. Kannan; T. Pushparaj (International Journal of Computer Sciences and Engineering, 2014)
Software testing is a crucial activity in software development and it determines to completeness of a product. Being a crucial activity it needs to be carried out smoothly without any difficulties. But in reality it is difficult to carry out testing smoothly. There exists number of factors and issues that alter the smooth happening of testing. Those factors and issues are collectively called as bottlenecks. This work aims at the process of identifying the bottlenecks that are very common to testing, bottlenecks that are application specific and testing type specific, analyse the reasons and provide recommendations that will make Software Testing[1] to happen without bottlenecks or with minimum bottlenecks. This work was carried out in two phases. Phase 1, was conducted to know and understand the existence of bottlenecks in software testing. Phase 2, deals with the analysis of bottlenecks and recommendations to avoid or minimize bottlenecks.